Targeted Violence: a Review of the Literature on Radicalization and Mobilization - McBride, Megan (Perspectives on terrorism, 2022)
This literature review contributes to the work of understanding the differences between targeted violence and domestic terrorism by exploring research on radicalization and mobilization processes within the literature on targeted violence. This review relied on the U.S. Department of Homeland Security’s 2019 terminology regarding the definition of targeted violence, and consequently focused on incidents that lacked an ideological motivation and occurred in "communities, schools, places of worship, and other public gatherings". Although our data collection returned 169 distinct articles seemingly on the radicalization or mobilization of those involved in terrorism and targeted violence, we did not find a robust discussion of processes of radicalization or mobilization of those who commit acts of targeted violence. We did, however, identify five "theories of radicalization" in the targeted violence literature which we review in this article. We then articulate recommendations for research that would improve understanding of how domestic terrorism and targeted violence are related in the US discourse. This work is especially critical because the literatures on these topics are not, at present, in conversation with one another, and bringing them together has the potential to meaningfully advance the understanding of both phenomena.